2021
DOI: 10.1111/njb.03104
|View full text |Cite
|
Sign up to set email alerts
|

ISSR genotyping of Phoenix theophrasti natural populations in Turkey and Crete (Greece) and P. dactylifera

Abstract: Intraspecific and interspecific diversity between Phoenix theophrasti individuals (92 from Turkey and 70 from Crete, Greece) and P. dactylifera specimens (28 from Turkey) were investigated by inter-simple sequence repeat (ISSR) analysis. A total of 45 polymorphic fragments, 360-3454 bps long, were produced. Intraspecific diversity for P. dactylifera was 26.63% and similarities ranged between 0.5 and 1. In the constructed dendrogram, P. dactylifera specimens clustered together in the first main group, outside b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…There are some indications that ISSR could be used to identify species. The ISSR results obtained by the authors of Boydak et al [ 46 ] supported the idea that the well-known date palms Phoenix theophrasti and P. dactylifera are different species. The ISSR marker system has also been used to determine molecular differences between two species of cotton [ 28 ].…”
Section: Discussionmentioning
confidence: 68%
“…There are some indications that ISSR could be used to identify species. The ISSR results obtained by the authors of Boydak et al [ 46 ] supported the idea that the well-known date palms Phoenix theophrasti and P. dactylifera are different species. The ISSR marker system has also been used to determine molecular differences between two species of cotton [ 28 ].…”
Section: Discussionmentioning
confidence: 68%
“…Gene flow can prevent or reduce genetic differences between populations accumulated by isolation, and frequent gene flow (Nm > 1.0) can prevent differentiation between populations caused by genetic drift. At Nm < 1.0, genetic drift is the dominant cause of differentiation among populations [34,36,39,40]. Our results show that the geneexchange level among the six wild populations of A. nanus is very low, which intensifies their inter-population genetic differentiation, and there is a clear trend of increase.…”
Section: Discussionmentioning
confidence: 69%
“…An UPGMA clustering map showed that the genetic distance between Akeqi and Ohsalur populations was the shortest, although the spatial distance between the two sites was the greatest. Previous studies showed that the genetic distance between populations was proportional to the spatial distance between them [34,36,39]; however, inconsistencies also existed in this relationship [35,40]. The Akeqi and Ohsalur populations are spatially remote but genetically close; thus, the two populations are genetically similar, possibly owing to genetically similar ancestors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…ISSR (Inter Simple Sequence Repeat), which is a PCR (Polymerase Chain Reaction) based molecular marker, primers with double, triple, quadruple and quintuple repetitive nucleotides are used, and the region between two microsatellites can be ampli ed with these primers (Zietkiewicz et al 1994). Because of their highly polymorphic nature, this technique aids in assessing variation among species and detecting population structure (Boydak et al 2021). ISSR markers have some advantages like primer design without knowledge of genomic sequence, the requirement of a small amount of DNA and low costs compared with RFLP (Restriction Fragment Length Polymorphism), SSR (Simple Sequence Repeat), and AFLP (Ampli ed Fragment Length Polymorphism) techniques.…”
Section: Introductionmentioning
confidence: 99%